Development and Evaluation of a WISE-Based Learning Model to Enhance Critical Thinking, Creativity, Collaboration, and Communication - Fatirul, Achmad Noor; Sabariah, Sabariah; Robani, Anidah; Rufi’i, Rufi’i; Prihatin, Prihatin (Journal of Educational Science and Technology (EST), 2025)
Critical thinking, creativity, collaboration, and communication skills are essential requirements in 21st-century education. Learning activities that integrate the habits of Wondering, Investigating, Synthesizing, and Expressing (WISE) are believed to enhance these skills among higher education students. However, the application of these habits in the learning context in Indonesia remains limited. Therefore, this study aims to develop a WISE-based learning product and evaluate its effectiveness. This study aims to develop and test the feasibility of a product that integrates WISE habits into learning to enhance students' critical thinking, creativity, collaboration, and communication skills. The research employed a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study included 50 students from the PGSD and Physical Education programs at Universitas PGRI Adi Buana Surabaya. Data were collected through expert evaluations of design, content, media, and instruments, as well as product trials on small, limited, and large groups. Data analysis utilized both quantitative and qualitative descriptive techniques. The results indicate that the WISE-based learning product received excellent evaluations from design, content, and media experts, as well as positive responses from students in all trial groups. WISE activities were proven effective in improving students' critical thinking, creativity, collaboration, and communication skills. In conclusion, the WISE-based learning product is deemed feasible for use and offers specific advantages, such as high visual appeal and strong relevance to real-world contexts. The application of this product can enhance students' skills in alignment with the demands of 21st-century education.